Preparation of spent bleaching earth-supported calcium from limestone as catalyst in transesterification of waste frying oil - Hindryawati, Noor; Daniel,; Erwin,; Gaanty Pragas, Maniam (Semarang State University, 2017)
An investigation was conducted on palm oil refinery waste-spent bleaching earth (POR-SBE), POR-SBE supported by calcium as catalysts for methyl esters production through transesterification process using waste frying oil. The catalysts showed longer lasting activity than the traditional alkali catalysts. The optimum conditions for the process were: Ca-PORSBE catalyst amount 7 %; methanol to oil molar ratio 12:1; and a reaction duration is 4 h. The process was able to transesterify oil to methyl esters at 96.8 % conversion at 65°C. The catalysts were easily separated from the reaction mixture and the final product met selected biodiesel fuel properties in accordance with European Standard EN 14214.